2020
DOI: 10.3390/nu12071929
|View full text |Cite
|
Sign up to set email alerts
|

NHANES 2011–2014 Reveals Cognition of US Older Adults may Benefit from Better Adaptation to the Mediterranean Diet

Abstract: Although the Mediterranean diet (MedD) has gained interest for potential Alzheimer’s disease (AD) prevention, it is unknown how well US older adults follow a MedD. We used two National Health and Nutrition Examination Survey (NHANES) cycles (2011–2014) to conduct our primary aim of reporting population estimates of MedD adherence among older adults (60+ years) in the US (n = 3068). The mean MedD adherence score for US older adults was 5.3 ± 2.1 (maximum possible = 18), indicating that older adults in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 35 publications
2
32
0
Order By: Relevance
“…Studies have indicated that various dietary patterns, including the Mediterranean diet (MedDi), Dietary Approaches to Stop Hypertension (DASH), Mediterranean-DASH diet Intervention for Neurological Delay (MIND), ketogenic diet, and caloric restriction may prevent or delay cognitive deterioration [ 28 ]. Several studies have shown that the higher the adherence to MedDi, the lower the risk of cognitive impairment and dementia [ 29 , 30 ]. Although the mechanisms underlying the proposed benefits of MedDi regarding preventing cognitive deterioration are not fully understood, several pathways may explain this neuroprotective effect, including reduction in oxidative stress and inflammation, interference with amyloid aggregation, improvement of cardiovascular health, modification of the gut microbiota, and stimulation of epigenetic modification [ 28 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have indicated that various dietary patterns, including the Mediterranean diet (MedDi), Dietary Approaches to Stop Hypertension (DASH), Mediterranean-DASH diet Intervention for Neurological Delay (MIND), ketogenic diet, and caloric restriction may prevent or delay cognitive deterioration [ 28 ]. Several studies have shown that the higher the adherence to MedDi, the lower the risk of cognitive impairment and dementia [ 29 , 30 ]. Although the mechanisms underlying the proposed benefits of MedDi regarding preventing cognitive deterioration are not fully understood, several pathways may explain this neuroprotective effect, including reduction in oxidative stress and inflammation, interference with amyloid aggregation, improvement of cardiovascular health, modification of the gut microbiota, and stimulation of epigenetic modification [ 28 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Descriptive statistics were presented as median and interquartile range (non-normally distributed continuous data), or mean and SD (approximately normally distributed continuous data), or percentages (categorical data). The association analyses were conducted using weighted least squares regression 43 with or without adjusting for covariates. Sub-analyses were conducted in the following sub-cohorts: participants aged 12–19 years or 20–80 years or perimenopausal women aged 47–56 years.…”
Section: Methodsmentioning
confidence: 99%
“…Descriptive statistics were presented as median and interquartile range (non-normally distributed continuous data), or mean and SD (approximately normally distributed continuous data), or percentages (categorical data). The association analyses were conducted using weighted least squares regression 37 writing -review and editing.…”
mentioning
confidence: 99%